Anxiety levels and quality of life assessment in patients that underwent an electrophysiologic study due to unexplained palpitations - Mehmet Fatih Özlü; Osman Yıldırım; Alim Erdem; Serkan Öztürk; Suzi Selim Ayhan; Fatih Canan; Mehmet Yazıcı (Türk Kardiyoloji Derneği Arşivi, 2013)
Objectives: To compare the quality of life and anxiety levels of patients with normal and abnormal results detected during an electrophysiological study (EPS) that was performed due to undocumented palpitations. Study design: Patients (n=128) who underwent EPS without documented arrhythmia of unexplained palpitations were included in the study. The quality of life and anxiety levels of patients with abnormal EPS results were compared with those with normal results by using the 26-item short form of the World Health Organization quality of life scale and statetrait anxiety inventory. Results: SVT was found in 72 patients by diagnostic EPS. Quality of life scores were significantly poorer in the SVT group than of the normal EPS group (p=0.000-0.001). Likewise, the anxiety scores of the patients in the SVT group were higher than normal in the EPS group (p=0.000). Age, physical quality of life, psychological quality of life, state anxiety and trait anxiety were found to be independent predictors of SVT in multivariate regression analysis. Conclusion: The level of anxiety was found to be higher and quality of life was found to be lower in patients with palpitations due to SVT. In clinical practice it should be kept in mind that noticed psychiatric symptoms may be secondary to an underlying arrhythmia in the evaluation of patients with palpitations.